2015
DOI: 10.1186/s12889-016-2718-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of additional follow-up telephone counseling in a smoking cessation clinic in Beijing and predictors of quitting among Chinese male smokers

Abstract: BackgroundNo previous studies have investigated whether additional telephone follow-up counseling sessions after face-to-face counseling can increase quitting in China, and whether this strategy is feasible and effective for promoting smoking cessation is still unclear.MethodsA non-randomized controlled study was conducted in Beijing. We compared the quit rates of one group which received face-to-face counseling (FC) alone (one session of 40 min) to another group which received the same face-to-face counseling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…A recent Cochrane review showed that individual behavioral counseling of >10 min significantly increases the likelihood of cessation by 40–60% than a minimal contact control (brief advice, usual care or provision of self‐help materials). Additional telephone follow‐up counseling sessions are also reported to double the quit rate at 12‐month follow up. A specialized counseling intervention has proved more effective for helping patients cease smoking than a usual state quit‐line.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…A recent Cochrane review showed that individual behavioral counseling of >10 min significantly increases the likelihood of cessation by 40–60% than a minimal contact control (brief advice, usual care or provision of self‐help materials). Additional telephone follow‐up counseling sessions are also reported to double the quit rate at 12‐month follow up. A specialized counseling intervention has proved more effective for helping patients cease smoking than a usual state quit‐line.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…Our study of the literature (summarised in Additional file 1 ) revealed that, while there was a paucity of research in this specific area, sub-optimal diabetes self-management (in general) among young people is likely driven by low socioeconomic status [ 39 ], low general and health literacy [ 39 ], low engagement with diabetes self-management education [ 20 , 39 41 ], cultural diversity of the priority population [ 42 ], optimistic bias and low risk perception [ 43 ], life-stage demands [ 44 ], high rates of diabetes-related distress [ 40 ] and complex healthcare needs [ 45 ].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The questionnaires were developed based on questionnaires used in the smoking cessation clinics of Hong Kong and Guangzhou [15][16][17], with minor revisions for more practical application in our smoking cessation clinic in Beijing [18]. The questionnaires were developed based on questionnaires used in the smoking cessation clinics of Hong Kong and Guangzhou [15][16][17], with minor revisions for more practical application in our smoking cessation clinic in Beijing [18].…”
Section: Data Collectionmentioning
confidence: 99%
“…Data were collected at the first visit and at 1 week, 1-, 3-, 6-and 12-month follow-up interviews using standardized, structured questionnaires. The questionnaires were developed based on questionnaires used in the smoking cessation clinics of Hong Kong and Guangzhou [15][16][17], with minor revisions for more practical application in our smoking cessation clinic in Beijing [18].…”
Section: Data Collectionmentioning
confidence: 99%